2016
DOI: 10.1111/jhn.12389
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary fibre intake with cancer and all‐cause mortality among 15 740 adults: the National Health and Nutrition Examination Survey III

Abstract: Dietary fibre showed protective benefits in terms of mortality risk. Investigating the mechanisms and components of dietary fibres underlying the different protective benefits remains an important consideration for research on fibre-mortality risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 34 publications
0
26
1
Order By: Relevance
“…The broader literature-based evidence related specifically to insoluble fiber and colorectal cancer remains inconsistent and is limited for supplemental insoluble prebiotics. Previous evaluation in the Nutrition Examination Survey (NHANES) III showed a protective effect for colorectal cancer mortality comparing high dietary insoluble fiber intake to low intake (45), which is contrary to our findings regarding supplemental insoluble fiber prebiotics. One large wheat bran fiber (an insoluble fiber) supplement trial in older (> 50 years) adults with a previous history of colonic polyps did not show any protective effect from insoluble fiber against recurrent colorectal adenomas (46).…”
Section: Discussioncontrasting
confidence: 99%
“…The broader literature-based evidence related specifically to insoluble fiber and colorectal cancer remains inconsistent and is limited for supplemental insoluble prebiotics. Previous evaluation in the Nutrition Examination Survey (NHANES) III showed a protective effect for colorectal cancer mortality comparing high dietary insoluble fiber intake to low intake (45), which is contrary to our findings regarding supplemental insoluble fiber prebiotics. One large wheat bran fiber (an insoluble fiber) supplement trial in older (> 50 years) adults with a previous history of colonic polyps did not show any protective effect from insoluble fiber against recurrent colorectal adenomas (46).…”
Section: Discussioncontrasting
confidence: 99%
“…While sugar intake was well within recommended limits for most participants, one unfavourable finding was the low intake of dietary fibre for both genders. Countless studies have investigated the importance of dietary fibre, of which many have found inverse associations with risk of CVD and all cancers (45)(46)(47) . Dietary fibre also promotes a healthy microbiota (48,49) .…”
Section: Discussionmentioning
confidence: 99%
“…The followup duration of cohorts ranged from 5 to 40 years. Twenty-five studies reported the results for total fiber, [28][29][30][31][32][33][49][50][51][52][53][54][55][56][57][60][61][62][63][64][66][67][68][69][70] 10 studies reported the results for fruit and vegetable fiber, 30,31,33,50,54,56,57,[63][64][65] 10 for cereal fiber, 30,31,33,50,51,[56][57][58]64,65 eight for soluble fiber, 30,31,33,50,52,55,…”
Section: Resultsmentioning
confidence: 99%
“…31,32,50,54,57,68,70 Three studies were conducted exclusively on women, 51,59,65 three on men, 28,64,67 and the others on both sexes. Nineteen studies used a food frequency questionnaire (FFQ) for dietary assessment, 28,30,31,[49][50][51]53,54,[56][57][58][59][60][61][62][63]65,66,68 three used 24 h dietary recall, 33,52,55 three used food records, 29,32,67 two used a dietary history questionnaire, 69,70 and one study implemented the cross-check dietary history method. 64 Of 28 prospective cohort studies, all studies were controlled for age and sex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation